2006
DOI: 10.1097/01.mlr.0000196975.52557.b7
|View full text |Cite
|
Sign up to set email alerts
|

Self-Advocacy During the Medical Encounter

Abstract: Although health information was associated with self-advocacy, black women were less likely to self-advocate. Further research is needed to better understand factors that impede black women from self-advocating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 38 publications
0
38
0
Order By: Relevance
“…For example, more than 8 in 10 (83%) of US Latinos obtain health information from the media, and 79% of those who do so act on that information (Livingston, Minushkin, & Cohn, 2008). Other studies have demonstrated significant positive effects of information-seeking from the media on health behaviors (Ramirez, Freres, Martinez, et al, 2013), improved doctor-patient communication (Rooks, Wiltshire, Elder, et al, 2012), and uncertainty management (Wiltshire, Cronin, Sarto, & Brown, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…For example, more than 8 in 10 (83%) of US Latinos obtain health information from the media, and 79% of those who do so act on that information (Livingston, Minushkin, & Cohn, 2008). Other studies have demonstrated significant positive effects of information-seeking from the media on health behaviors (Ramirez, Freres, Martinez, et al, 2013), improved doctor-patient communication (Rooks, Wiltshire, Elder, et al, 2012), and uncertainty management (Wiltshire, Cronin, Sarto, & Brown, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Cancer care education and self-advocacy skills sets can enable cancer survivors to overcome unique barriers (e.g., discrimination and stigmatization) [29], fostering self-care, symptom management and coping [30]. However, the effectiveness of self-advocacy depends greatly upon the survivor’s level of empowerment [22] and is affected by various factors, including personal characteristics and technical skills, the complexity of the patient’s illness [29, 31, 32], and availability and utilization of various forms of support [28].…”
Section: Self-advocacymentioning
confidence: 99%
“…However, the effectiveness of self-advocacy depends greatly upon the survivor’s level of empowerment [22] and is affected by various factors, including personal characteristics and technical skills, the complexity of the patient’s illness [29, 31, 32], and availability and utilization of various forms of support [28]. Therefore, in addition to self-advocacy education and training, some cancer patients and survivors may benefit from broader empowerment strategies and support.…”
Section: Self-advocacymentioning
confidence: 99%
“…Self advocacy has been conceptualized as the efforts of survivors to engage their own health experiences and overlaps with constructs such as healthcare-related self-efficacy and proactive postures [15-17]. Self-advocacy has been associated with improved cancer-related care outcomes among African American patients [17-21], potentially due to increased awareness of and responses to intrapersonal, interpersonal and systemic factors affecting them specifically (e.g., own distrust; discriminatory experiences with their providers), as conceptualized by social cognitive theories [22].…”
Section: Introductionmentioning
confidence: 99%
“…Self-advocacy has been associated with improved cancer-related care outcomes among African American patients [17-21], potentially due to increased awareness of and responses to intrapersonal, interpersonal and systemic factors affecting them specifically (e.g., own distrust; discriminatory experiences with their providers), as conceptualized by social cognitive theories [22]. Community/interpersonal advocacy has been conceptualized as the efforts of individuals and organizations to optimize cancer care experiences of specific patients with whom they are connected and overlaps with skill building, self-management, and navigation strategies [14,23].…”
Section: Introductionmentioning
confidence: 99%